A performance-based framework to prioritise underutilised historical buildings for adaptive reuse interventions in New Zealand. (July 2019) - Aigwi, Itohan Esther; Egbelakin, Temitope; Ingham, Jason; Phipps, Robyn; Rotimi, James; Filippova, Olga
Abstract: While the efficacy of salvaging underutilised historical buildings to promote sustainable and resilient provincial urban areas in New Zealand has been identified from past studies, there is still an absence of a performance-based framework to rank optimal historical building alternatives for adaptive reuse interventions. This paper focuses on evaluating a performance-based Multiple Criteria Decision Assessment (MCDA) methodology to prioritise underutilised historical buildings for adaptive reuse intervention in a major provincial area in New Zealand, towards achieving a resilient town-centre regeneration for the area. A focus group workshop was conducted with relevant stakeholders involved in an existing town centre regeneration agenda for Whanganui, to explore and balance their opinions for optimal selection of a vacant historical building for adaptive reuse intervention from a group of proposed buildings. The participant mix comprised a combination of building professionals, historical building owners/developers/users, legal, heritage, and council/community representatives. The findings establish the usefulness of the validated framework in balancing the diverse interests of all stakeholders in the adaptive reuse decision-making process. Hence, this paper provides a significant contribution to the development of a methodology that integrates adaptive reuse stakeholders' diversified interests, for the selection of optimal case study building alternatives. The consensus of the multidisciplinary stakeholder group was found to be consistent and insensitive to reasonable changes in weighting. Also, the validated framework enabled the decision-makers to achieve a logical result, and support the visualisation of the impact of different priority aspects and criteria on adaptive reuse interventions in New Zealand.